BASIC COMPETENCE ELEMENTS ANALYSIS OF 7 TH GRADE TEXTBOOK “WHEN ENGLISH RINGS THE BELL” - Rahadyan, Fakhri Muhammad; Rozy, Fery Fahrur; Nopriyanti, Irnella (Faculty of Education and Teachers Training, 2024)
In education, textbooks are a source of material that is very much needed by students, for that in designing textbooks, especially in terms of basic competencies, it must be considered. Whether the existing material meets the standards or the material presented includes all the basic skills. The research aimed to analyze the basic competence elements in